1997
DOI: 10.1074/jbc.272.11.7182
|View full text |Cite
|
Sign up to set email alerts
|

Human STX Polysialyltransferase Forms the Embryonic Form of the Neural Cell Adhesion Molecule

Abstract: PST and STX are polysialyltransferases that form polysialic acid in the neural cell adhesion molecule (N-CAM), although it is not known why these two polysialyltransferases exist. In the present study, we have first isolated cDNA encoding human STX, which includes 5-untranslated sequence. Northern blot analysis, using this cDNA and PST cDNA previously isolated by us, demonstrated that PST and STX are expressed in different fetal and adult tissues. STX is primarily expressed in embryonic tissues, but only modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
65
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 50 publications
(76 reference statements)
6
65
0
Order By: Relevance
“…We examined the effects of ManBut, a PSA synthesis inhibitor, on the neurite outgrowth of chick dorsal root ganglia neurons when cultured on a substratum of HeLa-NCAM/STX cells. Consistent with earlier studies, we found that neurite outgrowth was promoted by the polysialylation of NCAM on HeLa cell substrata (7,8,40). In one such experiment, summarized in Fig.…”
Section: Psa Inhibition By Manbut Reduces Neurite Outgrowth In Chick supporting
confidence: 81%
See 4 more Smart Citations
“…We examined the effects of ManBut, a PSA synthesis inhibitor, on the neurite outgrowth of chick dorsal root ganglia neurons when cultured on a substratum of HeLa-NCAM/STX cells. Consistent with earlier studies, we found that neurite outgrowth was promoted by the polysialylation of NCAM on HeLa cell substrata (7,8,40). In one such experiment, summarized in Fig.…”
Section: Psa Inhibition By Manbut Reduces Neurite Outgrowth In Chick supporting
confidence: 81%
“…Root Ganglion Neurons-The expression of polysialic acid on neural cells has a significant effect on cell migration and axon outgrowth (8,14,39). We examined the effects of ManBut, a PSA synthesis inhibitor, on the neurite outgrowth of chick dorsal root ganglia neurons when cultured on a substratum of HeLa-NCAM/STX cells.…”
Section: Psa Inhibition By Manbut Reduces Neurite Outgrowth In Chick mentioning
confidence: 99%
See 3 more Smart Citations